Determinantes de la pobreza desde una perspectiva macroeconómica - Diana Heuer Taborga; Horacio Villegas Quino; Francisco Javier Aliaga (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2015)
– This research approaches the poverty determinants from a macroeconomic perspective in Bolivia. The identity proposed by Bourguignon is analyzed; it simultaneously considers the economic growth and distribution effects on poverty. For this objective the considered literature relates macroeconomic variables, such as: income per capita, unemployment, investment and inflation poverty. Thus, the relationship between these variables will be verified by data panel methodology. Due to these tools income per capita, unemployment and social investment are effectively poverty determinants. Moreover, the relationships proposed by economic theory are verified.
Keywords: E6; C33; I32; 330